Development of over-MW gyrotrons for fusion at 14 GHz to sub-THz frequencies. (11th April 2017) - Kariya, T.; Imai, T.; Minami, R.; Sakamoto, K.; Oda, Y.; Ikeda, R.; Shimozuma, T.; Kubo, S.; Idei, H.; Numakura, T.; Tsumura, K.; Ebashi, Y.; et al.
Abstract: Megawatt power gyrotrons are being developed for collaborative electron cyclotron heating (ECH) studies of advanced fusion devices and demonstration power plant (DEMO). (1) In the first experiment of a 300 GHz gyrotron, an output power above 0.5 MW in the TE32, 18 single mode was achieved with a pulse width of 2 ms. This was the first observation of MW-scale oscillations in a DEMO-relevant gyrotron mode. It was also found that the reflection at the output window affected the determination of the oscillation mode. Furthermore, several single mode oscillations in the 226–254 GHz range were confirmed, which is important for the step-frequency tunable gyrotron in the sub-THz frequency range. (2) Based on the successful results of the 77 and 154 GHz large helical device (LHD) tubes, a new 154/116 GHz dual-frequency gyrotron with an output of over 1.5 MW is being designed. (3) A new record output of 1.38 MW was obtained using an existing 28 GHz gyrotron. A newly designed tube aimed at achieving a dual-frequency output power of 2 MW at 28 GHz (0.4 MW continuous wave) and 1 MW at 35 GHz was built. In the first experimental test, main mode oscillations were observed at the frequencies of 28.036 and 34.831 GHz with Gaussian-like output beams and output power of 1.27 and 0.48 MW, respectively. A total efficiency of 50% was achieved at 28 GHz operation.